The DAR 2020 Global survey: Ramadan fasting during COVID 19 pandemic and the impact of older age on fasting among adults with Type 2 diabetes. (March 2021) - Hassanein, Mohamed; Hussein, Zanariah; Shaltout, Inass; Wan Seman, Wan Juani; Tong, Chin Voon; Mohd Noor, Nurain; Buyukbese, Mehmet Akif; El Tony, Lobna; Shaker, Gamal Mohamed; Alamoudi, Reem M.; Hafidh, Khadija; Fariduddin, M.; et al.
Abstract: Objectives: The DAR Global survey of Ramadan-fasting during the COVID-19 pandemic aimed to describe the characteristics and care in participants with type 2 diabetes (T2D) with a specific comparison between those <65 years and ≥65 years. Methods: Participants were consented to answer a physician-administered questionnaire following Ramadan 2020. Impact of COVID-19 on the decision of fasting, intentions to fast and duration of Ramadan and Shawal fasting, hypoglycaemia and hyperglycaemia events were assessed. Specific analysis comparing age categories of <65 years and ≥65 years were performed. Results: Among the 5865 participants, 22.5% were ≥65 years old. Concern for COVID-19 affected fasting decision for 7.6% (≥65 years) vs 5.4% (<65 years). More participants ≥65 years old did not fast (28.8% vs 12.7%, <65 years). Of the 83.6%, participants fulfilling Ramadan-fasting, 94.8% fasted ≥15 days and 12.6% had to break fast due to diabetes-related illness. The average number of days fasting within and post-Ramadan were 27 and 6 days respectively, regardless of age. Hypoglycaemia and hyperglycaemia occurred in 15.7% and 16.3% of participants respectively, with 6.5% and 7.4% requiring hospital care respectively. SMBG was performed in 73.8% of participants and 43.5% received Ramadan-focused education. Conclusion: During the COVID-19 pandemic, universally high rates of Ramadan-fasting were observed regardless of fasting risk level. Glycemic complications occurred frequently with older adults requiring higher rates of acute hospital care. Risk stratification is essential followed by pre-Ramadan interventions, Ramadan-focused diabetes education and self-monitoring to reduce and prevent complications, with particular emphasis in older adults.